Experimental and analytical evaluation of bending for stainless steel - Mohd Hafizu, Hasan Basri (2012)
Analytical calculation is one of the methods in predicting the spring-back angle after bending process. Precise predictions of spring-back angle after the bending process are the key to the design of the bending die, bending tool, and to produce the accuracy part geometry. This thesis purpose is to determine the reliability of analytical method in V-bending analysis of stainless steel by comparing the results with experimental results and the experimental measurements of Özgür (2008). The effects of significant parameters including sheet thickness and sheet anisotropy on spring-back in V-bending analysis also have been studies. The mechanical properties that provided from tensile test experiment have been used in the analytical calculation in solving the spring-back equation. Two different equations from previous studies have been used to determine the spring-back angle. In the V-bending experiment, two different test procedures (bottoming and air V-bending process) were used. The experimental results have been used to evaluate the analytical results. The results of this project shown the spring-back values for analytical calculation are generally is not in agreement with the experimental value but the graph trends obtained in this study are generally in agreement with experimental graph patterns. The graph patterns are also in agreement with the past study by other researcher (Özgür, 2008). Increasing the sheet thickness resulted increase in the spring-back angle. The orientation angle and anisotropy value R will influence the spring-back. In general, the spring-back angle is increase if the orientation angle is increase. Therefore, the 0 degree orientation angle is a suitable condition in V-bending processes because the spring-back value is smallest compared to other orientation angles. The percentage error is very high because there are some errors occur during the tensile specimen preparation, tensile test experiment and V-bending test experiment. The accuracy and precision of machine in collecting and determined the data is a factors as the higher percentage error. It is conclude that the analytical method is not suitable in sheet metal bending analysis of stainless steel. This is because, combination of various material types and process parameters make the exact prediction of spring-back difficult.